Współczesne filmy biblijne (filmy o tematyce biblijnej) - zarys problematyki = Contemporary bible-inspired films - an outline of the problem - Ciupka, Stanisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The history of biblical subject matter in film productions seems to be as old as the existence of cinema. Our intention is to examine selected issues concerning biblical motifs in films at the turn of the second and third millenniums. We are convinced that biblical kontent has its place in today`s cinematic production.
Keywords: Jesus Christ; Bible; film; apocrypha; literature; Jezus Chrystus; Biblia; apokryfy; literatura